Effective hydrogen generator testing for on-site small engine - Praitoon Chaiwongsa; Nithiroth Pornsuwancharoen; Preecha P. Yupapin (My University, 2009)
We propose a new concept of hydrogen generator testing for on-site small engine. In general, there is a trade-off between simpler vehicle design and infrastructure issues, for instance, liquid fuels such as gasoline and methanol for small engine use. In this article we compare the hydrogen gases combination the gasoline between normal systems (gasoline only) for small engine. The advantage of the hydrogen combines gasoline for small engine saving the gasoline 25%. Furthermore, the new concept of hydrogen combination for diesel engine, bio-diesel engine, liquid petroleum gas (LPG), natural gas vehicle (NGV), which is discussed in details.
Keywords: Hydrogen vehicle; Liquefied petroleum gas; Hydrogen Storage and Materials